Low-threshold optically pumped lasing in highly strained germanium nanowires. Issue 1 (December 2017) - Bao, Shuyu; Kim, Daeik; Onwukaeme, Chibuzo; Gupta, Shashank; Saraswat, Krishna; Lee, Kwang Hong; Kim, Yeji; Min, Dabin; Jung, Yongduck; Qiu, Haodong; Wang, Hong; Fitzgerald, Eugene; et al.
Abstract The integration of efficient, miniaturized group IV lasers into CMOS architecture holds the key to the realization of fully functional photonic-integrated circuits. Despite several years of progress, however, all group IV lasers reported to date exhibit impractically high thresholds owing to their unfavourable bandstructures. Highly strained germanium with its fundamentally altered bandstructure has emerged as a potential low-threshold gain medium, but there has yet to be a successful demonstration of lasing from this seemingly promising material system. Here we demonstrate a low-threshold, compact group IV laser that employs a germanium nanowire under a 1.6% uniaxial tensile strain as the gain medium. The amplified material gain in strained germanium can sufficiently overcome optical losses at 83 K, thus allowing the observation of multimode lasing with an optical pumping threshold density of 3.0 kW cm−2 . Our demonstration opens new possibilities for group IV lasers for photonic-integrated circuits. Integrating group IV lasing devices into technologically relevant CMOS architectures has proven challenging. Here, the authors demonstrate low-threshold lasing, which is important for potential electronic and photonic circuits, using strained germanium nanowires as the gain material.